The sales performance of franchise managers in Avon-Iloilo Branch - Pragados, Geevah L.
The purpose of this study is to comprehend the sales performance of Franchise Manager AVPN-Iloilo Branch. Sales performance is the main statistical gauge and data that can predict the vitality of an organization engaged in product sales. performance in direct selling has become the main predictor in the overall performance of an organization engaged in sales. These products and services are marketed to customers by independent salespeople. Depending on the company, the salespeople may be called distributors, representatives, consultants or various other titles. Avon is a company that engages in direct selling and largely dependent on its people in the field. This company was established decades ago in the major urban centers of the Philippines including Iloilo City. How does Avon-Iloilo maintain or improve its sales performance? How does it develop its Franchise managers to achieve organizational goal? What are the support systems given to the Franchise Managers? Are the Franchise Managers made aware of such organizational support accorded them ? Are they appreciative of this support. This research will answer these questions. METHODS. Using purposive sampling method, thirty (30) respondents from the Franchise Managers of AVON-IloiloBranch were surveyed using a questionnaire. Primary data were collected through this questionnaire and secondary data were gathered through examining some of the relevant company literature. The data were treated statistically with the most appropriate method, the correlation analysis. RESULTS. Based on collated responses, the researchers presents the following: On the level of understanding of Franchise managers regarding their functions, it was found out that the respondents have a high level of understanding regarding their functions as Franchise Managers. This may be credited to them or to the company which was not lacking in doing its role in making them understand their functions. On Franchise manager's implementation of their functions effecting good sales performance, t was found out that most of the respondents agreed that they have implemented their functions in order to effect good sales performance. they believe that they are doing their job well, therefore there has to be some positive result to their output in terms of sales. On the level of understanding of Franchise managers regarding Avon's Sales Support Program for good sales performance, it appears that they have a high level of understanding regarding Avon's Sales Support Program. This means that they are aware of such programs and how they can affect sales. On the Franchise Manager's response towards the Sales support Program bringing about good performance in sales, it was discovered that the Franchise Managers responded positively towards the Sales Support Program implemented by the company. By such a response, the respondents appreciate the value f those programs and sed them in their own sales activities in order to help them improve their performance. On the level of awareness of the Franchise managers regarding the company's product sales promotions for good sales performance, most of the respondents have a high level of awareness regarding the company's product sales promotion activities. This can mean that they are aware of the company's activities wherein their products are being promoted. RECOMMENDATIONS. Other factors affecting the sales performance of Franchise Managers be looked into. Likewise, the process on the Franchise manager's implementation of their functions be evaluated in relation to their sales performance. And lastly, the Company's Sales Support Programs and product promotion activities must be enhanced extensively to be more effective.